Program Kerja Kampus Mengajar 6 Untuk Meningkatkan Literasi Siswa/I Di SDN 125/Ix Simpang Selat Melalui Membaca Lantang - Reni amalia; Nyimas Muazzomi (Jurnal Teknologi Pendidikan Dan Pembelajaran | E-ISSN : 3026-6629, 2023)
Reading aloud or what is called reading aloud reading aloud is the activity of reading by voicing picture or written text with clear speech, correct intonation so that listeners and readers can grasp the message correctly. The aim of carrying out this service activity is so that students are willing to listen to the stories being told so that it is hoped that interest in reading will arise and improve the way students read in terms of punctuation, intonation and pauses in reading within themselves. The research approach used in this research is outdoor study research. Outdoor study is a learning activity that uses nature directly as a learning resource to obtain various information about learning material. The evaluation results can be said to have increased literacy.